Los tiempos de Lucio V. Mansilla - Sandra Contreras (Cuadernos LIRICO)
The main purpose of this paper is to draw the map of interpretations, rewritings and uses of Lucio V. Mansilla’s literature and Lucio V. Mansilla’s name from the second half of the 19th century to the present. From Borges’ indifference to María Moreno’s fascination, a wide range of positions can be observed : David Viñas’ obsession, Osvaldo Lamborgnini’s and César Aira’s scenes, Osvaldo Baigorria’ narrative and the political action of young Kirchner supporters writing in Mancilla magazine. The aim of this article is to report on the importance of Mansilla as a writer of the 20th century, studying his presence in argentine criticism and literature in the last five decades.